Prevalence of Low Vitamin D in Patients with Breast Cancer in a Predominantly Hispanic Population at the American-Mexican Border. (18th August 2017) - Farrag, Safa E.; Dwivedi, Alok K.; Otoukesh, Salman; Badri, Nabeel J.; Sanchez, Luis A.; Nahleh, Zeina A.
ABSTRACT: Introduction : Low level of vitamin D (VD) has been linked with a higher risk of cancers. The aim of this study was to assess the prevalence of low VD in patients with breast cancer in a predominantly Mexican Hispanic/Latino patient population, a fast growing and relatively understudied population. Materials/Methods : We sought to evaluate the serum VD levels in breast cancer patients diagnosed at the Texas Tech University Breast Cancer Center in El Paso, TX, between May 2013 and May2014 via a retrospective chart review of the Electronic Medical Records. Results : We identified a total of 83 consecutive breast cancer patients with available VD levels. Mean age 57 yr, 94% were Hispanics. VD was insufficient (<30 ng/ml) in 86% of patients (95% CI: 0.76–0.92) and it was deficient (<20 ng/ml) in 39% (95% CI: 0.28–0.50). Conclusion : VD deficiency is widely prevalent in Hispanic/Latino patients with breast cancer. This is quite alarming in view of possible increased risk of cancer with low VD and potentially worse cancer outcomes. This calls for increased efforts to screen for, diagnose, and treat VD deficiency in this patient population. Further pharmacogenomics studies are warranted to explore the underlying etiology of VD deficiency in this paradoxically sunny region.